Fountain and gazebo - Gordon, John C. (photographer):::Creator::::::::::::
Photograph shows a low wall with hedges in front of it. On this wall a gargoyle in the shape of a carved lion's head spouts water into a basin below. Behind the wall stands a separate structure of columns, which may be a gazebo.